The male role in cervical cancer prevention and transmission: Representation of subject positions in South African press reports (1998-2014) - Moodley, Prevan; de Vries, Lauré (PINS-Psychology in Society, 2016)
Cervical cancer (CC) media coverage neglects mention and interrogation of the role of men in sexually transmitting the virus linked to CC. Newspapers, in their public role of engaging with social debates, unlike other media forms, might be expected to interrogate misconceptions of CC. This study sought to analyse how male persons are represented in newspaper reports of CC. Using the discursive analytic tool of subject positioning, South African newspaper reports of CC were analysed. The findings revealed five categories of subject positions with male persons serving as protagonists who interact with subjects in the remaining four categories. In the male subjects’ category, the unaccountable man and circumcised saviour were the most commonly occurring positions. Reportage, however, also covered male positions traditionally marginalized or excluded from public and mainstream health campaigns, and the most pertinent of these were labelled as the sex-talk son and the boy saviour. CC should be conceptualized not merely as a health issue faced by individual women, but as a social issue with a need for increased public visibility of the male role in transmission and prevention.